Macroeconomic Conditions and Pressures for Protection Under Antidumping and Countervailing Duty Laws : Empirical Evidence from the United States - Leidy, Michael (IMF Working Papers; Working Paper ;, 1996)
Antidumping and countervailing duty procedures are governed by specific rules requiring both injury (by reason of imports) and dumping/subsidies, and thus might be expected to be less susceptible to pressures for protection arising from cyclical movements in the domestic macroeconomy. This paper investigates whether there is a connection between the state of domestic macroeconomic activity and pressures for protection under antidumping and countervailing duties. The evidence suggests that pressures for protection under these measures since the Tokyo Round of multilateral trade talks have advanced during periods of macroeconomic weakness and receded during periods of macroeconomic strength.